Factor influencing the preferences of Generation Y towards working at remote area : Case study at Murum Hydroelectric Plant, Sarawak Energy Berhad / Daisy James - James, Daisy (2019)
As baby boomers exit the workforce and Generation Y are here already and they will be a force in the next 20 years. As generation evolve, value, attitudes, mindsets and behaviour change, and same goes to the work preferences. Since Generation Y has become widespread, regardless among marketers and employers it is necessary to pay attention to this particular cohort generation especially towards the factors that influence the working preferences such as organizational attractiveness, work values and job satisfaction and digitalization and technology practices. This research aim to study the factors influencing the Preference among eighty five (85) staff(the Generation Y) towards Working at the Remote Area (Murum Hydroelectric Plant). The study structured use extensive literature review to explore factor influencing the preference of generation Y towards working at remote areas by collected data based on questionnaire distributed and analyse using predictive analytic software which know as Statistical Package for Social Science Software (SPSS). This study will provide inside on the relationship of all the factors that contribute to the preferences of Generation Y that opted to work at remote area (Murum Hydroelectric Plant). Finding of this study may assist the organization to identify and implies the needs (preferences) of the affected staffthat working in hydro plant.